CONTROLLING THE MUHAMMADIYAH LHOKSEUMAWE ORPHANAGE IN FORMING INDEPENDENT CHARACTER OF FOSTER CHILDREN - Almuhajir Almuhajir (JURNAL AL-TANZIM, 2021)
The formation of children's independent character is one of the goals of education that is wanted to be realized in the educational process, both in formal, non-formal and informal educational institutions. This study aims to explain controlling the Muhammadiyah Lhokseumawe Orphanage in forming the independent character of foster children. This research is a qualitative research using a phenomenological approach. The results showed that controlling the Muhammadiyah Lhokseumawe Orphanage in forming an independent character included controlling the Chair of the Caregivers which consisted of the Caregiver's personality and materials or learning methods with two approaches, namely direct confirmation of Caregiver and foster children in formal and non-formal situations. Caregiver Controlling of Foster Children which consists of cognitive aspects, namely the ability to understand and master learning material, affective aspects, namely changes in the behavior of foster children in their daily life, and psychomotor aspects, namely the ability of foster children to develop skills or talents.